A pilot study comparing ergonomics in laparoscopy and robotics: beyond anecdotes, and subjective claims. Issue 2 (21st February 2020) - Kuo, Li-Jen; Ngu, James Chi-Yong; Lin, Yen-Kuang; Chen, Chia-Che; Tang, Yue-Her
Abstract: We aimed to use hand dexterity and grip strength test as objective measures to compare the difference in surgeon fatigue associated with robotic and laparoscopic colorectal surgery. We used the Purdue Pegboard Test to assess hand dexterity and the Camry Electronic Handgrip Dynamometer to assess hand grip strength. Eighteen patients were operated on, including 10 robotic and 8 laparoscopic cases. Statistical analysis revealed no difference in dexterity or muscle fatigue after operating with the robot. In contrast, there was a significant difference in the hand grip strength of both hands after laparoscopic surgery. Our results show that the resultant fatigue after laparoscopy affects both hands of the surgeon. In contrast, there was no difference in dexterity or muscle fatigue after operating with the robot. Given the demands of complex colorectal surgeries, robotics may be a means of optimizing surgeon performance by reducing fatigue.